Alpha-gal syndrome: first case reported in Peru - Alva-Lozada , Guisela (2025)
We present the case of a 5-year-old male patient with a medical history of recurrent bronchospasms since 3 months . He went to the pediatric allergy clinic at the Edgardo Rebagliati Martins National Hospital with his mother, who reported episodes of acute urticaria, one after consuming cooked pork and another 2 after consuming cooked beef. To the evaluation, non-contributory exam. The following tests were performed: specific IgE in vitro, where a positive result was obtained for pork albumin (26.6 KUA/L) and later skin tests, with a positive result for raw pork. Due to the appearance of lesions only after the consumption of cooked mammalian meat, alpha-gal syndrome was suspected and specific IgE testing against alpha-gal was requested through an external laboratory, which came back positive (>100 kU/L).